Niacin promotes the efflux of lysosomal cholesterol from macrophages via the CD38/NAADP signaling pathway. Issue 12 (June 2022) - Yang, Shenghua; Zhang, Fan; Li, Quanwen; Li, Quanzhong
The accumulation of free cholesterol in macrophage lysosomes significantly enhances atherogenesis. Our recent study demonstrated that the cluster of differentiation 38 (CD38)/nicotinic acid adenine dinucleotide phosphate (NAADP)/Ca 2+ signaling pathway plays a critical role in the efflux of lysosomal free cholesterol from macrophages in atherosclerosis. Niacin, known as nicotinic acid, is one of the oldest lipid-lowering medications showing unique anti-atherosclerotic activity. However, it is unknown whether this anti-atherosclerosis activity is associated with the efflux of lysosomal compartmentalized cholesterol in macrophages. In this study, we investigated the anti-atherosclerotic effects of niacin on the reduction of lysosomal free cholesterol via CD38/NAADP signaling in macrophages derived from low-density lipoprotein receptor (LDLr −/− ) mice. Fluorescent filipin and Nile red labeling coupled with confocal microscopy demonstrated that niacin reduced free cholesterol accumulation in lysosomes in a concentration-dependent manner. Transmission electron microscopy also showed that niacin markedly decreased cholesterol crystal formation in lysosomes in oxidized LDL-containing LDLr −/− bone marrow–derived macrophages. Enzyme-linked immunosorbent assays showed that niacin increased NAADP production in a concentration-dependent manner, which was inhibited by small interfering RNA interference of CD38. Therefore, niacin may promote the efflux of lysosomal cholesterol from macrophages via the CD38/NAADP signaling pathway.